2018
DOI: 10.1016/j.dib.2018.06.050
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical, biochemical and nutritional characterisation of 42 organic wastes and residues from France

Abstract: The data presented in this article regroup characterisation of organic matter and nutritional composition of 42 organic wastes and residues usually used as substrates for anaerobic digestion. Those wastes have different origins from agro-industrial, agricultural and urban sectors in France including: algae, slaughterhouse waste, fat, food waste, fruits and vegetables residues, green waste, slurry, manure, wastewater treatment plant sludge and agricultural residues. The properties of organic matter are distingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 4 publications
1
1
0
Order By: Relevance
“…The C/N ratio of FW was between 6.5 and 12.37. In terms of elementary composition, as well as the chemical oxygen demand (COD) of about 1600 g COD/kg VS, FW showed a similar range for landbased investigations by Heo et al [43], Zhang et al [44], Curry and Pillay [45] and Fisgativa et al [46]. However, those authors reported higher C/N ratios in a range from 13 to 18.…”
Section: Chemical Characterisation Of Substratessupporting
confidence: 65%
“…The C/N ratio of FW was between 6.5 and 12.37. In terms of elementary composition, as well as the chemical oxygen demand (COD) of about 1600 g COD/kg VS, FW showed a similar range for landbased investigations by Heo et al [43], Zhang et al [44], Curry and Pillay [45] and Fisgativa et al [46]. However, those authors reported higher C/N ratios in a range from 13 to 18.…”
Section: Chemical Characterisation Of Substratessupporting
confidence: 65%
“…Lightweight substrate with low organic content requires additional fertilisers and water to establish sustainable vegetation (Getter & Rowe, 2006 ). Furthermore, organic wastes possess high plant nutrient content than the recycled aggregates (Fisgativa et al, 2018 ; Soobhany, 2019 ), ideal water retention (S. Kumar et al, 1985 ), optimum pH, and drought resistance of (Anli et al, 2020 ) the attributes essential for healthy horticulture. Therefore, the iteration of available organic wastes to find a comprehensive substrate would be a profitable approach in terms of sustainability.…”
Section: Introductionmentioning
confidence: 99%